2020
DOI: 10.21203/rs.3.rs-42042/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quality of life of patients living with psoriasis: a qualitative study

Abstract: Background: Psoriasis is a multifactorial inflammatory disease prevalent in dermatology. We aimed to understand the perceptions of patients living with psoriasis in relation to their quality of life and to identify aspects to improve it. Methods: This is qualitative research carried out in a dermatology outpatient clinic of the São Paulo State University (UNESP) medical school, Botucatu, Brazil, with 81 psoriasis patients. The interviews were transcribed and analysed using the Discourse of the Collective Subje… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…So, those patients report that doctors are not prepared to face the situation and minimize the problem, leaving them with feelings of rejection and with the gravity of their problems underestimated. Hence, there is a great need to support the individual issues of their lives beyond illness (18) as cited at (19) .…”
Section: Resultsmentioning
confidence: 99%
“…So, those patients report that doctors are not prepared to face the situation and minimize the problem, leaving them with feelings of rejection and with the gravity of their problems underestimated. Hence, there is a great need to support the individual issues of their lives beyond illness (18) as cited at (19) .…”
Section: Resultsmentioning
confidence: 99%
“…Psoriasis can have an effect on patient psychological and social well-being due to symptoms and the visibility of the affected area. 17,18 Addressing individual, team, and systemic gaps could provide psoriasis patients with more coherent, patient-centered care and thus reduce the impact of the disease on their quality of life. Although the current study revealed collaborative gaps between primary care providers, dermatologists, and rheumatologists, it would be beneficial for optimal patient care to ensure HCPs collaborate strategically and effectively with mental health professionals in educational interventions.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, improved pruritus and lesion visibility might be the major contributions in patient's satisfaction in addition to safety concerns. 31 So improved plaque severity and the decreased pruritus with topical cyclosporine would improve patient's quality of life suggesting that this treatment method would be clinically useful.…”
Section: Discussionmentioning
confidence: 99%